The role of facilitator training in intervention delivery: Preparing clinicians to deliver AFFIRMative group cognitive behavioral therapy to sexual and gender minority youth. Issue 1 (2nd January 2021) - Craig, Shelley L.; Iacono, Gio; Austin, Ashley; Eaton, Andrew D.; Pang, Nelson; Leung, Vivian W. Y.; Frey, Cressida J.
Abstract: Cognitive behavioral therapy (CBT) promotes sexual and mental health risk reduction. Tailored affirmative approaches, where facilitators validate participants' lived experiences, can bolster CBT's potential to improve coping and mood, especially for sexual and gender minority youth (SGMY). Specialized training better prepares clinicians to deliver affirmative CBT and contributes to implementation fidelity. This paper describes a standardized facilitator training for clinicians to deliver an affirmative CBT group intervention to SGMY. The AFFIRM training consists of fourteen hours of didactic and simulation-based learning. Study participants ( n = 129) represented diverse professional, sexual, gender, and ethnoracial identities with a particular focus on community-based practitioners. To evaluate training effectiveness, The Affirmative CBT Facilitator Competence Scale (ACCS; 7-items, α = 0.922), designed for this study was completed by participants. Paired sample t-tests showed a significant difference between pre ( M = 18.14, SD = 5.90) and post training scores ( M = 25.97, SD = 6.34); t (128) = −16.21, p < .001). Thematic analysis of qualitative feedback identified two major themes strengthened ability to affirm SGMY identities and increased competence to deliver AFFIRM. The training increased the skills of a diverse group of clinicians to facilitate affirmative CBT to SGMY.